Effects of Mat Feeding on the Growth Performance and Mortality of Pigs After Weaning - Madie R. Wensley; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Jason C. Woodworth; Joel M DeRouchey; Matt Allerson; Mariana Menegat (Kansas Agricultural Experiment Station Research Reports, 2021)
Three experiments were conducted to determine the effect of different mat feeding strategies on the growth performance and morbidity and mortality of pigs after weaning. Upon arrival to the nursery facility, pigs were randomized to pen. A total of 96 pens (48 feeders) with 30 to 35 pigs/pen were used for each experiment, with one barrow pen and one gilt pen per feeder. Thus, feeder (2 pens) was the experimental unit. Feeders were then blocked by group (date of placement) and randomly allotted to treatment. In Exp. 1, treatments consisted of two feed management strategies; mat feeding vs. no mat feeding. Overall, a tendency was observed for ADG (P= 0.056) with mat fed pigs having poorer ADG compared to the control group, which resulted in decreased (P<0.026) final body weights. No differences were observed in ADFI or feed efficiency. Mat fed pigs had reduced total removals (P= 0.019) compared to the control group. In Exp. 2, treatments were arranged in a 2 × 2 factorial with main effects of diet form (pellet or crumble) and mat feeding (without or with). No interactions between diet form and mat feeding were observed. No differences were observed in overall growth performance for the main effect of mat feeding, but for diet form, pigs that received pelleted feed had decreased overall ADFI(P= 0.013) and improved feed efficiency (P<0.001). No differences were observed in total removals. In Exp. 3, treatments consisted of three feed management strategies: mat feeding small (1/8 in.) pellets, mat feeding large (1/2 in.) pellets, and no mat feeding. No differences were observed in overall ADG or feed efficiency; however, mat fed pigs had increased ADFI (P<0.05), regardless of pellet size. Although not statistically significant, mat feeding the small pellets reduced the total removal rate by 2.1 percentage points compared to the control group, and 1.2 percentage points compared to mat feeding the large pellets. When combining the removal and mortality data for the three experiments, mat fed pigs had fewer total removals (P= 0.025) compared to the control group. In summary, mat feeding has limited effects on the growth performance of pigs after weaning; however, mat feeding may encourage earlier feed intake, therefore reducing the morbidity and mortality rate of pigs.
Keywords: performance; pig; mat feeding; mortality; weaning